Pulmonary myeloid cell uptake of biodegradable nanoparticles conjugated with an anti-fibrotic agent provides a novel strategy for treating chronic allergic airways disease. (June 2021) - Chakraborty, Amlan; Pinar, Anita A.; Lam, Maggie; Bourke, Jane E.; Royce, Simon G.; Selomulya, Cordelia; Samuel, Chrishan S.
Abstract: Asthma (chronic allergic airways disease, AAD) is characterized by airway inflammation (AI), airway remodeling (AWR) and airway hyperresponsiveness (AHR). Current treatments for AAD mainly focus on targeting AI and its contribution AHR, with the use of corticosteroids. However, there are no therapies for the direct treatment of AWR, which can contribute to airway obstruction, AHR and corticosteroid resistance independently of AI. The acute heart failure drug, serelaxin (recombinant human gene-2 relaxin, RLX), has potential anti-remodeling and anti-fibrotic effects but only when continuously infused or injected to overcome its short half-life. To alleviate this limitation, we conjugated serelaxin to biodegradable and noninflammatory nanoparticles (NP-RLX) and evaluated their therapeutic potential on measures of AI, AWR and AHR, when intranasally delivered to a preclinical rodent model of chronic AAD and TGF-β1-stimulated collagen gel contraction from asthma patient-derived myofibroblasts. NP-RLX was preferentially taken-up by CD206 + -infiltrating and CD68 + -tissue resident alveolar macrophages. Furthermore, NP-RLX ameliorated the chronic AAD-induced AI, pro-inflammatory cytokines (IL-1β, IL-6, TNF-α), chemokines (CCL2, CCL11) and the pro-fibrotic TGF-β1/IL-1β axis on AWR and resulting AHR, as well as human myofibroblast-induced collagen gel contraction, to a similar extent as unconjugated RLX. Hence, NP-RLX represents a novel strategy for treating the central features of asthma.